2016
DOI: 10.15376/biores.11.4.9068-9078
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Saccharification of Cellulose using a Cellulase Mixture and Supplemental β-glucosidase in Aqueous-Ionic Liquid Media

Abstract: In situ enzymatic saccharification is one promising approach to efficiently convert non-food biomass to glucose as a platform chemical. The goal of the present research was to illustrate the catalytic behaviors and deactivation mechanisms of cellulase and cellobiase in an aqueous-ionic liquid (IL) media. The hydrolysis reaction rate was considerably increased because of the increased porosity and reduced crystallinity of the substrate. To lower the inhibitory effect of accumulated cellobiose on cellulase, a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Figure shows the XRD patterns of catalysts. In Figure A, peaks of cellulose at 16° and 35° almost disappeared after ionthermal pretreatment and were transformed into an amorphous halo peak at 22° by comparison of (1) microcrystal cellulose, (2) BC precursor, and (3) BC. These results demonstrated that cellulose crystallinity was significantly decreased and BC porosity was therefore enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the XRD patterns of catalysts. In Figure A, peaks of cellulose at 16° and 35° almost disappeared after ionthermal pretreatment and were transformed into an amorphous halo peak at 22° by comparison of (1) microcrystal cellulose, (2) BC precursor, and (3) BC. These results demonstrated that cellulose crystallinity was significantly decreased and BC porosity was therefore enhanced.…”
Section: Resultsmentioning
confidence: 99%